Courtroom Context and Sentencing - Arazan, Christine L. (American journal of criminal justice, 2019)
This study provides an evaluation of the major policy shift in sentencing practices over the past half-century – namely the shift from indeterminate to determinant sentencing policies and the use of sentencing guidelines. The theoretical literature on courtroom organization and focal concerns informs this evaluation of determinate sentencing practices in Florida. Drawing from prior theoretical and empirical research, hierarchical linear and generalized linear models are estimated to assess courtroom effects on individual level sentencing outcomes. The findings document that location matters when sentenced in Florida. Specifically, the likelihood of being sentenced to prison and the length of sentence varies across counties, even after controlling for individual case and offender characteristics and a variety of contextual characteristics. Additionally, the influence of legal and extra-legal factors on prison in/out and sentence length decisions varies significantly across counties. Several court characteristics, including court size, caseload pressure and trial rate assert direct influence on a county’s likelihood of prison in/out and mean sentence length decisions.